Mapping the Gaps: A Scoping Review of Virtual Care Solutions for Caregivers of Children with Chronic Illnesses - Nicole Pope; Kathyrn A. Birnie; Melanie Noel; Justine Dol; Danyu Li; Megan Macneil; Darrel Zientek; Victoria Surry; Jennifer N. Stinson (Children)
Background/Objectives: Caregivers of children with chronic illnesses, including chronic pain, experience high levels of distress, which impacts their own mental and physical health as well as child outcomes. Virtual care solutions offer opportunities to provide accessible support, yet most overlook caregivers’ needs. We conducted a scoping review to create an interactive Evidence and Gap Map (EGM) of virtual care solutions across a stepped care continuum (i.e., from self-directed to specialized care) for caregivers of youth with chronic illnesses. Methods: The review methodology was co-designed with four caregivers. Data sources were the peer-reviewed scientific literature and a call for innovations. Records were independently coded and assessed for quality. Results: Overall, 73 studies were included. Most virtual care solutions targeted caregivers of children with cancer, neurological disorders, and complex chronic illnesses. Over half were noted at lower levels of stepped care (i.e., self-guided apps and websites), with psychological strategies being predominant (84%). However, very few addressed caregivers’ physical health (15%) or provided family counseling (19%) or practical support (1%). Significant gaps were noted in interventions for managing caregiver chronic pain, despite its high prevalence and impact on child outcomes. Conclusions: Evidence and Gap Maps are innovative visual tools for knowledge synthesis, facilitating rapid, evidence-informed decision-making for patients, families, health professionals, and policymakers. This EGM highlighted high-quality virtual care solutions ready for immediate scaling and identified critical evidence gaps requiring prioritization. To address the complexities of pediatric chronic illnesses, including chronic pain, virtual care initiatives must prioritize family-centered, accessible, and equitable approaches. Engaging caregivers as partners is critical to ensure interventions align with their needs and priorities.